RELATIONSHIP BETWEEN DEMOGRAPHIC CHARACTERISTICS AND SPIRITUAL WELLBEING AMONG CANCER SURVIVORS - Eviwindha Suara; Mardiyono Mardiyono; Anggorowati Anggorowati (Belitung Raya Foundation, Indonesia, 2017)
Background: Spiritual wellbeing (SWB) is an important quality-of-life dimension for cancer patients. Therefore, health professionals are demanded to improve SWB in these patients. A deeper understanding regarding the factors associated with SWB is needed. Objective: This study aims to examine the relationships of demographic characteristics of patients and spiritual wellbeing in patients with cancer. Methods: This was a cross-sectional correlational study with 60 respondents recruited using consecutive sampling. A spiritual wellbeing scale (SWBS) was used, and data were analyzed using Kendall's Tau and Spearman's rank. Results: Findings in this study showed that only age was statistically significant with spiritual wellbeing of cancer patients with p-value 0.003 (<0.05). There were no significant relationships of gender, education, occupation, long suffering, and type of cancers with spiritual wellbeing with p-value >0.05. Conclusion: There was a significant relationship between age and spiritual wellbeing in patients with cancer. This study provides the insight of knowledge regarding the factors affecting spiritual wellbeing in patients with cancer.